The Effectiveness of Augmented Reality-Assisted Scientific Approach to Improve Mathematical Creative Thinking Ability of Elementary School Students - Ahmad Arifuddin; Wahyudin Wahyudin; Sufyani Prabawanto; Muhamad Yasin; Desi Elizanti (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to determine the effectiveness of the scientific approach assisted by augmented reality in improving students' mathematical creative thinking ability. This research is a quasi-experimental study with a pretest-posttest control group design. The participants in this study were 5th-grade students in 2 (two) integrated Islamic elementary schools in Cirebon City, Indonesia, with a total of 47 students. The data in this study were collected through a mathematical creative thinking ability test that refers to fluency, originality, flexibility, and elaboration indicators. Then the data that collected was analyzed through descriptive, n-gain test, and Mann Whitney tests. The results showed that there was a significant difference in the n-gain score of students' mathematical creative thinking skills between the experimental group using a scientific approach assisted by augmented reality and the control group using direct instruction learning assisted by augmented reality, where the U value was 129.5, the value was 129.5. Z of -3.380, and the value of Sig. (2-tailed) of 0.001 < 0.05. The mean score of n-gain and posttest score of mathematical creative thinking ability of experimental group students was significantly higher than that of the control class. So the scientific approach assisted by augmented reality effectively improves students' mathematical creative thinking skills..Keywords: mathematical creative thinking, scientific approach, direct instruction, augmented reality. AbstrakPenelitian ini bertujuan untuk menentukan efektifitas pendekatan saintifik berbantuan augmented reality dalam meningkatkan kemampuan berpikir kreatif matematis siswa. Penelitian ini merupakan penelitian kuasi-eksperimen dengan desain pretest-posttest control group desain. Partisipan dalam penelitian ini adalah siswa kelas 5 di 2 (dua) sekolah dasar Islam terpadu di Kota Cirebon, Indonesia yang berjumlah 47 siswa. Data dalam penelitian ini dikumpulkan melalui tes kemampuan berpikir kreatif matematis yang mengacu pada indikator kelancaran, keluwesan, fleksibilitas, dan elaborasi. Kemudian data yang telah dikumpulkan dianalisis melalui uji deskriptif, uji n-gain, dan uji mann whitney. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan dalam skor n-gain kemampuan berpikir kreatif matematis siswa antara kelompok eksperimen yang menggunakan pendekatan saintifik berbantuan augmented reality dengan kelompok kontrol yang menggunakan pembelajaran direct instruction berbantuan augmented reality, di mana nilai U sebesar 129,5, nilai Z sebesar -3,380, dan nilai Sig. (2-tailed) sebesar 0,001 < 0,05. Rerata skor n-gain dan skor posttest kemampuan berpikir kreatif matematis siswa kelompok eksperimen secara signifikan lebih tinggi dari pada kelas kontrol. Sehingga dapat disimpulkan bahwa pendekatan saintifik berbantuan augmented reality efektif meningkatkan kemampuan berpikir kreatif matematis siswa. Kata kunci: berpikir kreatif matematis, pendekatan saintifik, direct instruction, augmented reality.